2007
DOI: 10.1021/bi7001532
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transitions in Human Very-Low-Density Lipoprotein:  Fusion, Rupture, and Dissociation of HDL-like Particles

Abstract: Very low-density lipoproteins (VLDL) are metabolic precursors of low-density lipoproteins (LDL) and a risk factor for atherosclerosis. Human VLDL are heterogeneous complexes containing triacylglyceride-rich apolar lipid core and polar surface comprised of phospholipids, a nonexchangeable apolipoprotein B, and exchangeable apolipoproteins E and Cs. We report the first stability study of VLDL. Circular dichroism and turbidity data reveal an irreversible heat-induced VLDL transition that involves formation of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(86 citation statements)
references
References 36 publications
3
83
0
Order By: Relevance
“…The uncertainly in this value incorporates the fi tting errors and the deviations among the data sets recorded from different batches of LDL. Notably, this value of E a is nearly twice as high as the maximal values obtained from heat denaturation studies of human HDL ( 35 ) or VLDL ( 36 ). High activation energy of LDL denaturation refl ects a steep temperature dependence of its rate constant, k(T), and explains why LDL heat denaturation could be monitored in a relatively narrow temperature range.…”
Section: Lipoprotein and Apolipoprotein Preparationmentioning
confidence: 88%
See 4 more Smart Citations
“…The uncertainly in this value incorporates the fi tting errors and the deviations among the data sets recorded from different batches of LDL. Notably, this value of E a is nearly twice as high as the maximal values obtained from heat denaturation studies of human HDL ( 35 ) or VLDL ( 36 ). High activation energy of LDL denaturation refl ects a steep temperature dependence of its rate constant, k(T), and explains why LDL heat denaturation could be monitored in a relatively narrow temperature range.…”
Section: Lipoprotein and Apolipoprotein Preparationmentioning
confidence: 88%
“…I). Thermal denaturation studies revealed that stability of LDL and other lipoproteins is determined by kinetic barriers and suggested that similar barriers modulate lipoprotein remodeling and fusion in vivo ( 30,(33)(34)(35)(36). In fact, the products of the heatinduced LDL fusion are similar in size and morphology to LDL-derived extracellular deposits in early atherosclerotic lesions ( 37 ).…”
Section: Circular Dichroism and Turbidity Measurementsmentioning
confidence: 99%
See 3 more Smart Citations